THE EXISTENCE OF ELECTRONIC EVIDENCE IN VERIFICATION LAW SYSTEM IN INDONESIA FROM THE JUDGEâS PERSPECTIVE - Adi Sulistiyono, Dedy Muchti Nugroho, Setiono & (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2017)
To find out the verification of civil case and criminal case in Republic ofIndonesiaâs Law No.11 of 2008 about Information and Electronic Transaction.Conclusions: (1) in civil case using electronic evidence, the evidence that islegitimate and can be revealed in the verification process is determined based onArticle 5 clause (1) and (2) of Law Number 11 of 2008 about Information andElectronic Information confirming that information and or electronic documentcan be considered as a legitimate evidence in verification process particularly incivil case using electronic evidence, the evidence is the expansion of evidence asregulated and enacted in the civil case law corresponding to the provision ofArticle 1866 BW. (2) The verification of crime should ensure that the existingelectronic document came from electronic system meeting the requirement basedon the legislation and after the enactment of ITE Law, there is an addition ofevidence and the recognition of electronic document as a legitimate evidencedetermining that electronic document or its print out is the legitimate evidence thatcan be used before the trial as long as the information contained within it can beaccessed, displayed, and ensured for its completeness and accountable for therebyinforming a condition. In addition, the position of electronic document isequalized to the document prepared on a piece of paper as mentioned in GeneralExplanation of ITE Law.